Hearing-impaired academic rifle shooting sport: self-suggestion with ideomotor training model for competitive progress - Krivtsov, A. S.; Nechushkin, Yu. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to test and analyze benefits of a new self-suggestion with ideomotor training model for academic hearing impaired rifle shooting sport